Adipocytokine Associations with Insulin Resistance in British South Asians. (25th February 2013) - Webb, D. R.; Khunti, K.; Chatterjee, S.; Jarvis, J.; Davies, M. J.
Abstract : Aims . Adipocytokines are implicated in the pathogenesis of type 2 diabetes and may represent identifiable precursors of metabolic disease within high-risk groups. We investigated adiponectin, leptin, and TNF- α and assessed the contribution of these molecules to insulin resistance in south Asians. Hypothesis . South Asians have adverse adipocytokine profiles which associate with an HOMA-derived insulin resistance phenotype. Methods . We measured adipocytokine concentrations in south Asians with newly diagnosed impaired glucose tolerance or Type 2 Diabetes Mellitus in a case-control study. 158 (48.5% males) volunteers aged 25–75 years with risk factors for diabetes but no known vascular or metabolic disease provided serum samples for ELISA and bioplex assays. Results . Total adiponectin concentration progressively decreased across the glucose spectrum in both sexes. A reciprocal trend in leptin concentration was observed only in south Asian men. Adiponectin but not leptin independently associated with HOMA-derived insulin resistance after logistic multivariate regression. Conclusion . Diasporic south Asian populations have an adverse adipocytokine profile which deteriorates further with glucose dysregulation. Insulin resistance is inversely associated with adiponectin independent of BMI and waist circumference in south Asians, implying that adipocytokine interplay contributes to the pathogenesis of metabolic disease in this group.